Ammonium increases Ca2+ signalling and upregulates expression of Cav1.2 gene in astrocytes in primary cultures and in the in vivo brain. (18th April 2015) - Wang, F.; Du, T.; Liang, C.; Verkhratsky, A.; Peng, L.
Abstract Aim The primary aim of this study was to identify the effects of hyperammonaemia on functional expression of Cav1.2 L‐type Ca2+ channels in astroglia. Methods Primary cultures of mouse astrocytes were used to study effects of chronic treatment (1–5 days) with ammonium chloride, at 1, 3 and 5 mm on depolarization‐induced increases in free cytosolic Ca2+ concentration ([Ca2+]i, measured with Fura‐2 based microfluorimetry) in control conditions and following treatment with the L‐type Ca2+ channel inhibitor, nifedipine, or with ryanodine receptor inhibitor, ryanodine. Expression of Cav1.2 mRNA was identified with RT‐PCR, whereas protein content was determined by Western blotting. Sustained hyperammonaemia in vivo was induced by daily injections of urease (33 units kg body weight−1, i.p.) for 3 days. Results Depolarization‐induced [Ca2+]i transients sensitive to nifedipine (peak of the response) and to ryanodine (plateau phase) were significantly increased in astrocytes chronically exposed to ammonium. The ammonium‐induced increase in Ca2+ influx in astrocytes resulted from an upregulation of Cav1.2 channel's expression detected at mRNA and protein levels. Increase in Cav1.2 expression was prevented by ouabain antagonist canrenone. Similar upregulation of Cav1.2 gene expression was found in the brains of adult mice subjected to intraperitoneal injection of urease. In transgenic mice tagged with an astrocyte‐specific or neurone‐specific markers and treated with intraperitoneal injections of urease, the fluorescence‐activated cell sorting of neurones and astrocytes demonstrated that Cav1.2 mRNA expression was upregulated in astrocytes, but not in neurones. Conclusions Ammonium‐induced deregulation of astroglial Ca2+ signalling, is, in part, associated with upregulation of Cav1.2 L‐type calcium channels.